Analisis Kemampuan Berpikir Kritis Siswa Kelas XI pada Materi Larutan Elektrolit dan Non Elektrolit - Sely Artasasta Lawongo; Tri Santoso; Magfirah Magfirah; Afadil Afadil; Dewi Satria Ahmar (Media Eksakta, 2022)
This study aims to analyze the critical thinking skills of students of class XI MIPA SMA Negeri 5 Palu on the material of Electrolyte and Non-Electrolyte Solutions. This research is a descriptive research. The sample of this study was 60 students of class XI MIPA SMA Negeri 5 Palu. The data collected was in the form of critical thinking ability test results obtained by giving questions in essay form as many as 7 valid questions. Furthermore, the data collected was analyzed based on indicators of critical thinking skills which include interpretation, analysis, inference, and evaluation respectively 45.50%, 27.08%, 27.08%, and 23.54%. The average result for all indicators of critical thinking ability of students in class XI MIPA is 32.53%. This shows that the critical thinking skills of class XI students of SMA Negeri 5 Palu are still lacking.